Text Messaging Items as an Assessment Tool for Certain Language Skills - Babista, Juancho M. (JPAIR Multidisciplinary Research, 2009)
This study attempted to determine the effectiveness of test messaging items for certain language skills. It sought to find out what skills can be measured by text messaging test items, to determine the efficiency of text messaging items for testing certain language skills, and the effectiveness of the testing instruments in assessing certain language performance. The research employed written text analysis. A sample test composed of three sets of text messages in three forms, Filipino text, Taglish text, and English text messages were made. A short paragraph in Filipino, Taglish, and English were transcribed into text messages by senior Education students who are majoring in English. After comparisons, they came up with the best text translation of the items. The test items were administered to freshmen Education students of the Southern Luzon State University. The subjects were asked to transcribe the messages in complete sentences. Results reveal that text messaging test items measure the respondents' competencies in reading comprehension, grammatical structures, phonetic ability, and usage. Based from the computed mean for different skills, the study revealed that the students have high level of comprehension in three languages used, high level of ability in grammatical structure in Filipino and average level of ability in grammatical construction in English; high level of ability in phonetics in Filipino and English based from their spelling of words; and high level of ability in correct usage based from their sentence construction.
Keywords: text messaging; reading skills; language skills